2008
DOI: 10.1371/journal.pone.0003508
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Inhibits Glyoxalase 1—A Possible Link to Its Anti-Inflammatory and Anti-Tumor Activity

Abstract: BackgroundGlyoxalases (Glo1 and Glo2) are involved in the glycolytic pathway by detoxifying the reactive methylglyoxal (MGO) into D-lactate in a two-step reaction using glutathione (GSH) as cofactor. Inhibitors of glyoxalases are considered as anti-inflammatory and anti-carcinogenic agents. The recent finding that various polyphenols modulate Glo1 activity has prompted us to assess curcumin's potency as an Glo1 inhibitor.Methodology/Principal FindingsCultures of whole blood cells and tumor cell lines (PC-3, JI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 62 publications
(71 reference statements)
3
117
1
2
Order By: Relevance
“…The activity of glyoxalase I may be modulated by various polyphenols, e.g. curcumin is a strong competitive inhibitor of glyoxalase I with concomitant antiinflammatory activity 34 . Curcumin was shown to inhibit the growth of breast and prostate cancer and brain astrocytoma and could be a promising anticancer compound.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%
“…The activity of glyoxalase I may be modulated by various polyphenols, e.g. curcumin is a strong competitive inhibitor of glyoxalase I with concomitant antiinflammatory activity 34 . Curcumin was shown to inhibit the growth of breast and prostate cancer and brain astrocytoma and could be a promising anticancer compound.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%
“…In 2002 it was demonstrated a sensitized cytotoxic effect of BCNU with ß -glucan in PC3 PCa cells, which was associated with a drastic (approximately 80%) inactivation of Glo1 [63]. More recently, it has been also reported that curcumin inhibits Glo1 with the consequent intracellular accumulation of non-tolerable levels of MG and GSH, that, by modulating various metabolic cellular pathways, hamper malignant cells growth [64]. Finally, more recently, Baunacke et al [53] identified ethyl pyruvate as agent targeting Glo1 and defanging some malignancy-associated properties of PCa cells and Valenti et al [65] found that 3-bromopyruvate induced rapid human PCa cell death by affecting, among the others, Glo1.…”
Section: Glo1mentioning
confidence: 99%
“…Hence, in PCa, utilization of specific inhibitors of Glo1 might indeed serve as an effective anticancer strategy. Several natural compounds have been proposed as Glo1 inhibitors attenuating the growth of PCa [53,[62][63][64][65].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] One of the most employed compounds that are derivatives of S-(N-aryl-N-hydroxycarbamoyl) glutathione originally prepared by Creighton and colleagues. [4][5][6][7][8] For example, compounds 1-3 are good inhibitors of human GLO1 (hGLO1), with reported comparable K i value of 46, 10, and 14 nM, respectively (Fig.…”
Section: Design Synthesis and Biological Evaluation Of Potent Humanmentioning
confidence: 99%
“…To our delight, compound 4 exhibited K i value of 8 nM against hGLO1, which is determined by us recently. Some other important natural products have also been widely utilized as a hGLO1 inhibitor, such as delphinidin, 9) anthocyanidin, 9) methyl gerfelin (M-GFN), 10) curcumin, 11) and flavonoides.…”
Section: Design Synthesis and Biological Evaluation Of Potent Humanmentioning
confidence: 99%